การพัฒนาแบบประเมินภาวะผู้นำของพยาบาลหัวหน้าหอผู้ป่วยโรงพยาบาลสังกัดกระทรวงกลาโหม - สมพิศ เกิดศิริ (จุฬาลงกรณ์มหาวิทยาลัย, 1999)
The purposes of this research were to develop the leadership assessment scale for head nurses, hospital under the jurisdiction of the Ministry of Defence. There were two groups of population, 210 head nurses and their subordinates, 2, 160 staff nurses from 33 hospitals under the jurisdiction of the Ministry of Defence all over the country. A sample of 205 head nurses who have had at least a year of experience, was selected through the purposive sampling technique, and a sample of 970 staff nurses who worked as subordinates of the head nurses for at least a year, was selected through systemic sampling technique. The two instruments to be tested were rating scale on frequency of activities and demonstration of certain qualities, developed and adapted from the research result of Wasinee Wisesrith (1996). The first instrument, head nurses leadership questionnaire as expected for staff nurses was used to identify leadership factors by using principal component factor analysis, orthogonal rotated axis by varimax method. The second instrument, head nurses leadership assessment scale, developed from the results of factor analysis. Each of head nurse was assessed her leadership by her 3 subordinates through the second instrument. Two test were conduct. The first test was to discover reliability, standard error of measurement and discrimination indices. The second test was to discover reliability, standard error of measurement, discrimination indices and a normalized T-score norm. The major findings were as follows. Nine significant leadership factors of head nurses were identified: 1) charisma, 2) inspiration, 3) empowerment, 4) management by exception, 5) intellectual stimulation, 6) contingent reward, 7) change facilitator, 8) vision and projecting the vision and 9) individual consideration. The total variance of these factors was 61.53%. The reliability of each factor, calculated by the cronbach s alpha coefficient, range from .8006-.9566 and the reliability of the entire assessment scale was .9819. The standard error of measurement of the entire assessment scale was .104 and the discrimination indices of each test item were significant at .05 level. The raw score and normalized T-score of the entire assessment scale range from 3.18-4.93 and 21-78 respectively. The raw score and normalized T-score of each factor range from 2.33-5 and 21-78 respectively.